2016
DOI: 10.2135/cropsci2015.07.0466
|View full text |Cite
|
Sign up to set email alerts
|

Yield Response to Planting Date Among Soybean Maturity Groups for Irrigated Production in the US Midsouth

Abstract: Planting date is one of the main factors affecting soybean (Glycine max [L.] Merr.) yield. Environmental conditions in the US Midsouth allow for planting dates from late March through early July, and maturity groups (MGs) ranging from 3 to 6. However, the complexity of interactions among planting date, MG, and the environment makes the selection of an optimum MG cultivar difficult. A regional 3‐yr study, conducted at eight locations with latitudes ranging from 30.6 to 38.9°N, planting dates ranging from late M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 31 publications
(55 reference statements)
6
44
2
Order By: Relevance
“…Secondly, this study characterized both shoots as well as root growth and development to determine the temperature tolerance in the soybean cultivars. The present study evaluated soybean cultivars belonging to MG III, IV, and V, which are recommended ideal for the US Midsouth environments based on previous literature describing the interactive effects of agronomic practices, environments, and MG [2,16,19,20,[34][35][36]. The present study showed vigorous seedling growth in cultivars belonging MG IV and V when compared to MG III, which supports recent studies that favored MG IV and V to utilize under ESPS in the US Midsouth [2,19].…”
Section: Discussionsupporting
confidence: 86%
“…Secondly, this study characterized both shoots as well as root growth and development to determine the temperature tolerance in the soybean cultivars. The present study evaluated soybean cultivars belonging to MG III, IV, and V, which are recommended ideal for the US Midsouth environments based on previous literature describing the interactive effects of agronomic practices, environments, and MG [2,16,19,20,[34][35][36]. The present study showed vigorous seedling growth in cultivars belonging MG IV and V when compared to MG III, which supports recent studies that favored MG IV and V to utilize under ESPS in the US Midsouth [2,19].…”
Section: Discussionsupporting
confidence: 86%
“…A large planting date and soybean MG study was conducted at seven locations in 2012 and nine locations in and across the Midsouth. The locations were: Columbia, MO (38.9°N) 2016).…”
mentioning
confidence: 99%
“…Pairwise correlations between yield (lb/ac), seed growth rate (SGR, mg/seed / d), effective filling period (derived from SGR; EFP, d), dry matter allocation coefficient (DMAC, d -1 ), harvest index (HI, %), effective filling period 2 (derived from DMAC; EFP2, d), seed N concentration (%), average seed weight (ASW, mg), and planting day of year (PDOY, d). 2008; Salmerόn et al, 2016). However, DMAC had a weakly positive correlation to PDOY (p < 0.001; r = 0.40).…”
Section: Correlationsmentioning
confidence: 92%